Decision‐making biases in suicide attempters with major depressive disorder: A computational modeling study using the balloon analog risk task (BART). Issue 12 (3rd November 2022) - Liu, Qinyu; Zhong, Runqing; Ji, Xinlei; Law, Samuel; Xiao, Fan; Wei, Yiming; Fang, Shulin; Kong, Xinyuan; Zhang, Xiaocui; Yao, Shuqiao; Wang, Xiang
Abstract: Background: In the last decade, suicidality has been increasingly theorized as a distinct phenomenon from major depressive disorder (MDD), with unique psychological and neural mechanisms, rather than being mostly a severe symptom of MDD. Although decision‐making biases have been widely reported in suicide attempters with MDD, little is known regarding what components of these biases can be distinguished from depressiveness itself. Methods: Ninety‐three patients with current MDD (40 with suicide attempts [SA group] and 53 without suicide attempts [NS group]) and 65 healthy controls (HCs) completed psychometric assessments and the balloon analog risk task (BART). To analyze and compare decision‐making components among the three groups, we applied a five‐parameter Bayesian computational modeling. Results: Psychological assessments showed that the SA group had greater suicidal ideation and psychological pain avoidance than the NS group. Computational modeling showed that both MDD groups had higher risk preference and lower ability to learn and adapt from within‐task observations than HCs, without differences between the SA and NS patient groups. The SA group also had higher loss aversion than the NS and HC groups, which had similar loss aversion. Conclusions: Our BART and computational modeling findings suggest that psychological pain avoidance and loss aversion may be important suicide risk factor that are distinguishable from depression illness itself.